1. The problem statement, all variables and given/known data Prove: if a[itex]\neq[/itex]0 then b/a=b*a^-1 I don't know if my proof is sufficient with this one but I cannot think of another way. Also I am only supposed to use the basic axioms (e.g. commutative, distributive, existence of reciprocal...) 2. Relevant equations 1/a=a^-1 (I am not supposed to use this) Distributive law 3. The attempt at a solution b/a=b*(1/a) =b*(a^-1) =b*a^-1 I am not allowed to use the (1/a)=a^-1 thing, but I can't think of how to tackle this one any other way. Could someone at least get me pointed in the right direction? I am confused because the property seems too obvious hahaha.